Find the sum of first nine terms of the sum 1 1 3 + 1 + 3 1 3 + 2 3 + 1 + 3 + 5 1 3 + 2 3 + 3 3 .......
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
This was level 5?
1st term : 1 2 1 2 = 1
2nd term : 2 2 3 2 = 4 9
3rd term : 3 2 6 2 = 9 3 6
4th term : 4 2 1 0 2 = 1 6 1 0 0
5th term : 5 2 1 5 2 = 2 5 2 2 5
6th term : 6 2 2 1 2 = 3 6 4 4 1
7th term : 7 2 2 8 2 = 4 9 7 8 4
8th term : 8 2 3 6 2 = 6 4 1 2 9 6
9th term : 9 2 4 5 2 = 8 1 2 0 2 5
s u m = 1 + 4 9 + 9 3 6 + 1 6 1 0 0 + 2 5 2 2 5 + 3 6 4 4 1 + 4 9 7 8 4 + 6 4 1 2 9 6 + 8 1 2 0 2 5 = 9 6
It is a very lengthy method to solve such a question..
Problem Loading...
Note Loading...
Set Loading...
Each term a n is equal to:
a n = 1 + 3 + . . . 2 n − 1 1 3 + 2 3 + . . n 3
a n = 2 ( 2 n − 1 + 1 ) n ( 2 n ( n + 1 ) ) 2
a n = 4 ( n + 1 ) 2
The sum of the first K terms is:
S K = n = 1 ∑ K a n
S K = 4 1 n = 1 ∑ K ( n + 1 ) 2
Setting m = n + 1
S K = 4 1 m = 2 ∑ K + 1 m 2
S K = 4 1 ⎝ ⎛ m = 1 ∑ K + 1 m 2 − 1 ⎠ ⎞
S K = 4 1 [ 6 ( K + 1 ) ( K + 2 ) ( 2 K + 3 ) − 1 ]
S K = 2 4 2 K 3 + 9 K 2 + 1 3 K
We're looking for S 9 :
S 9 = 2 4 2 ⋅ 9 3 + 9 ⋅ 9 2 + 1 3 ⋅ 9
S 9 = 9 6